The Effect of Halal Foods Awareness on Purchase Decision with Religiosity as a Moderating Variable - Anggraini, Inar; Dewanti, Diah Setyawati (Journal of Economics Research and Social Sciences, 2020)
This study aims to examine and explain the effect of halal food awareness on purchase decisions with religiosity as a moderating variable. The sample in this study is Muslim consumers in Indonesia and Thailand. Purposive sampling technique was applied by criteria of samples required is Muslim consumers in Indonesia and Thailand. The number of samples is 200 respondents, included 150 Indonesian respondents and 50 Thai respondents. The analysis is done using Moderated Regression Analysis (MRA) with SPSS 23.0 software. The finding of this study shows that respondent has a high-level awareness of halal foods in Indonesia and Thailand. Halal food awareness has a positive and significant impact on purchase decisions for Muslims living in Indonesia. Halal food awareness has a positive and significant impact on purchase decisions for Muslims living in Thailand. Finally, the higher level of religiosity cannot strengthen the effect of awareness on a purchase decision.